Pragmatic Competence in the Spoken English Classroom - Krisnawati, Ekaning (Indonesian Journal of Applied Linguistics, 2011)
Abstract: Learnersâ€™ ability in carrying out communicative activities is highly demanded in the spoken English classroom. This paper discusses some aspects that should be taken into account when conducting a spoken English class in relation to raising pragmatic awareness through the inclusion of pragmatic instruction in the classroom. Some theoretical reviews for the inclusion of pragmatic instruction are also discussed. Through the inclusion of instruction in pragmatics in the spoken English classroom, learners are expected to develop their pragmatic competence and, therefore, are able to communicate naturally despite the fact that the full range of interactions with native speakers is limited. Â  Key words: communicative activity, pragmatic instruction, pragmatic competence